Karakteristik Sosial Ekonomi Rumah Tangga Petani Bawang Merah di Kecamatan Cibitung Kabupaten Sukabumi - Juniarti, Dhea Amalia (LPPM Universitas Malikussaleh - Indonesia, 2025)
This study aims to analyze the socio-economic characteristics of shallot farming households in Cibitung Subdistrict, Sukabumi Regency. A qualitative descriptive method was used. Respondents were selected through purposive sampling, with a total of 30 shallot farmers participating in the study. The results show that most farmers are of productive age but have limited farming experience and low levels of formal education. Shallot cultivation is conducted on a small scale, with an average land size ranging from 0.02 to 0.04 hectares, and a productivity rate of 3,017 kg/ha. Although production volume is relatively low, the relatively high selling price offers income opportunities. The main source of capital is personal funds, while the marketing system remains dominated by middlemen. All respondents are members of farmer groups, which serve as a source of information and cooperation. However, none are members of village unit cooperatives (KUD), as there are no active cooperatives in the area. In addition to farming (on-farm) activities, some farmers also engage in off-farm and non-farm work to supplement their income. These findings highlight the need to strengthen farmers’ capacity through training, institutional support, and improvements in the marketing system to enhance the sustainability of shallot farming.